Allometric relationship and growth models of juveniles of Cichlasoma festae (Perciforme: Cichlidae), a freshwater species native in Ecuador - Rodríguez, Jorge M.; Angón, Elena; González, Martín A.; Perea, José; Barba, Cecilio; García, Antón (Revista de Biología Tropical, 2017)
Ecuador is considered the fishing capital of the Southeastern tropical Pacific with more than 900 native species. Cichlasoma festae represents an economic important freshwater species of much local use. Thus, in this study, our goal was to characterize this fish species during juvenile stages, as the first step for its conservation and valuation, and also for the preparation of proposals for sustainable rural development and formulation of plans for environmentally responsible fisheries management. The study lasted 25 weeks and was undertaken in the ictiohidrographic area of Province of Los Rios, which accounts for 35 % of native fish species in Ecuador. Weekly, the individual biometric parameters total length (L), body width (BW) and body depth (BD) of 90 juveniles of C. festae were measured. Growth was determined using non-linear biological regression models. The average standard length varied between 6.30 cm and 12.25 cm and the average weight varied between 4.99 and 35.71 g. The length-weight relationship was best fit by the equation <!--?mso-application progid="Word.Document"?--> 15 lnW=-3.92+2.96 ln(L)"> , and the species presented negative allometric growth. Finally, the best fit for the growth of C. festae was the Von Bertalanffy’s model where <!--?mso-application progid="Word.Document"?--> 15Lâˆž"> = 19.758 cm, k = 0.028 cm week-1 and <!--?mso-application progid="Word.Document"?--> 15t0 "> = -14.463 week-1. We concluded that to support sustainable and reliable fisheries production studies, the growth record from length may be obtained with standard methods as those evaluated in this study, or may be obtained with new safer tools such as photogrammetry.